Therapeutic targeting of the host-microbiota-immune axis: implications for precision health - Nazir, Asiya; Hussain, Fathima Hasnain Nadeem; Nadeem Hussain, Tuahir Hassan; Al Dweik, Rania; Raza, Afsheen (Frontiers in Immunology, 2025)
The human body functions as a complex ecosystem, hosting trillions of microbes that collectively form the microbiome, pivotal in immune system regulation. The host-microbe immunological axis maintains homeostasis and influences key physiological processes, including metabolism, epithelial integrity, and neural function. Recent advancements in microbiome-based therapeutics, including probiotics, prebiotics and fecal microbiota transplantation, offer promising strategies for immune modulation. Microbial therapies leveraging microbial metabolites and engineered bacterial consortia are emerging as novel therapeutic strategies. However, significant challenges remain, including individual microbiome variability, the complexity of host-microbe interactions, and the need for precise mechanistic insights. This review comprehensively examines the host microbiota immunological interactions, elucidating its mechanisms, therapeutic potential, and the future directions of microbiome-based immunomodulation in human health. It will also critically evaluate challenges, limitations, and future directions for microbiome-based precision medicine.